(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
International Cooperation In Combating Cybercrime Has Two Aspects. The First Concerns The Need To Cooperate In Law Enforcement To Prosecute, And Punish Criminals After Committing The Crime, Which Cross Jurisdictions With Different Legal Systems, Namely, Judicial Cooperation. . The Second Aspect Of International Cooperation In Combating Cybercrime Is Technical Cooperation. International Cooperation Is Not Limited To Mutual Judicial Assistance, But Also Involves Technical Assistance And The Exchange Of Experience Between States. Keywords- Cybercrime - INTERPOL - United Nations – Extradition - Illegal Access